Análise dos nascimentos de filhos de estrangeiras em Mato Grosso entre 2007 e 2016 - Santos, Paola Marques da Costa (2019)
In Brazil, there is an increasing process of reception of immigrants. In this context, migratory experiences can make their impact on maternal health diverse, since they have cultural, psychosocial and biological specificities. Several countries have conducted research on the impact of immigration on the birth of children of immigrants, but in Brazil, studies on immigrants are still scarce. This study aimed to analyze the live births of foreign and Brazilian women living in Mato Grosso between 2007 and 2016, according to the mother's nationality. It is a cross-sectional study of secondary data, with an analysis of the birth records of the Information System on Live Births in Mato Grosso between 2007 and 2016, of Brazilian children born to Brazilian and foreign mothers. The variables of interest investigated were related to the sociodemographic information of the mother (maternal nationality, age, maternal schooling, marital status and parity), prenatal data (month of onset and number of consultations), birth and newborn information, (gestational age at birth, type of birth, birth weight, Apgar score). It was estimated the temporal trend of births of children of foreigners in the period from 2007 to 2016, using a polynomial regression and the spatial distribution of these births by health region. The data were stored and analyzed by the Statistical Package for Social Science (SPSS). Poisson regression was used to evaluate the association of nationality with low birth weight and prematurity, controlling for potential confounding factors. Between 2007 and 2016 occurred 1,123 births of children of foreigners in Mato Grosso (0,22% of total NV in the period). South and Central America stood out with 792 and 252 births (70% and 22.4%, respectively), with the three main nationalities being Bolivian, Paraguayan and Haitian. There was an increasing tendency of births of children of immigrants, with the main nationalities and the health regions with the highest number of children born to foreigners were Baixada Cuiabana and Matogrossense West. When comparing the characteristics evaluated according to the mother's nationality, a higher proportion of Haitians in the highest age group was observed, and the proportion of mothers who started prenatal care late among foreigners, especially among Bolivians, was higher, as was the proportion of mothers Bolivian and Haitian women who performed less than 6 prenatal consultations. Paraguayan (PR= 0.95; 95%CI=0.93; 0.97) and Bolivian (PR= 0.95; 95%CI=0.95; 1.00) nationality was inversely associated with low birth weight, however, Haitian nationality was positively associated (PR=1.05 95% CI= 1.00; 1.10). The results did not appear uniformly among the three main foreign nationalities, which reinforces the need for studies that address the specificities of each nationality.